DNA damage and ALAD polymorphism in high blood lead (Pb) levels of pregnant women attending a tertiary care teaching hospital - Mahesh Chandra Sahu; Kuldip Upadhyay; Shweta Gupta; Kabita Chanania; Sanghamitra Pati (Elsevier, 2024)
Abstracts: Background: Pregnant women are particularly vulnerable to lead toxicity due to increased absorption and decreased elimination of lead from their bodies. The δ-aminolevulinic acid dehydratase (ALAD) gene plays a crucial role in lead metabolism, and its polymorphisms have been implicated in modifying the susceptibility to lead toxicity. Methods: A cross-sectional study was conducted involving 90 pregnant women and blood samples were collected to measure blood lead levels (BLL) and assessed DNA damage using the comet assay. ALAD polymorphisms were genotyped using PCR-RFLP analysis with MspI restriction enzyme. Statistical analysis, including chi-square tests, logistic regression, and correlation analysis, was performed to determine associations between ALAD polymorphisms, BLL, and DNA damage. Results: From 90 pregnant women the participants, 16 had high BLL (≥5 μg/dL), while the remaining 74 had normal levels (<5 μg/dL). The ALAD 1-2 genotype was found to be significantly associated with high BLL (p < 0.001). Pregnant women with the ALAD 1-2 genotype exhibited higher levels of DNA damage compared to those with other genotypes (p < 0.001). Furthermore, a positive correlation was observed between the transfer of lead concentration from mother to infant and DNA damage severity (r = 0.511, p < 0.001). Conclusions: The combination of comet assay and polymorphism analysis offers a comprehensive approach to understanding the impact of lead exposure during pregnancy. These findings underscore the urgent need for effective regulatory measures to reduce lead exposure in the environment and mitigate its adverse effects of lead on maternal and child health.